Saṃyukta prānta ke Śikshā Vibhāga kī Mārca 31 san 1937 Ī. ko samāpta hone vāle pāñca sāla kī riporṭa - Mohammada Hanīfa, B.A (Suparinṭenḍenta, Prinṭinga va Sṭeśanarī, 1940)
Education in the United Provinces of Agra and Oudh, India during the period 1932-1937.